A afetividade na educação infantil: uma análise documental a partir da base nacional comum curricular - Suavi, Leticia Nayra [UNESP] (Universidade Estadual Paulista (Unesp), 2018)
The present work deals with the importance of affectivity in the teaching-learning process of the child in the stage of Early Childhood Education, seeking from this perspective to analyze the National Common Curricular Base (NCCB), focusing its structuring, as well as its approaches on the theme of affectivity, from its organization and mandatory contents presented in the stage of Early Childhood Education. The National Curricular Common Base is a document that aims to establish the essential knowledge that all students of Basic Education should learn, so that all schools are public or private networks of the country should contemplate in their curricula the contents presented in the document. Because it is a common guiding document for all the schools in the country from which all of them will build their curricula, all the contents and approaches presented by the Base are extremely important for education, thus being a reference for the construction of individual curricula of all Brazilian schools, it is necessary to consider the theme presented; the importance of affectivity in the teaching-learning process especially in the stage of Early Childhood Education in which this dimension is extremely present. We present the relevance of the theme to the context of Early Childhood Education, followed by an analysis of the existence of the same in the cited document and later the way the subject is addressed in this document. In order to develop and support the analysis of the theme proposed in this work, we use Henri Wallon psychogenetic theory, which considers the human development process from an integral perspective, in which affectivity is one of the determining factors in this process.

presente trabalho aborda a importância da afetividade no processo de ensino-aprendizagem da criança na etapa da Educação Infantil, buscando a partir dessa perspectiva analisar a Base Nacional Comum Curricular (BNCC), enfocando sua estruturação, bem como suas abordagens acerca do tema da afetividade, a partir de sua organização e conteúdos obrigatórios apresentado na etapa da Educação Infantil. A Base Nacional Comum Curricular é um documento que tem como objetivo estabelecer os conhecimentos essenciais que todos os alunos da Educação Básica devem aprender, assim, todas as escolas sejam elas de redes públicas ou privadas do país devem contemplar em seus currículos os conteúdos apresentados no documento. Por ser um documento norteador comum para todas as escolas do país a partir do qual todas elas construirão seus currículos, todos os conteúdos e abordagens apresentados pela Base possuem extrema importância para a educação, assim, sendo ela é referência para a construção dos currículos individuais de todas as escolas brasileiras é preciso considerar a temática apresentada; a importância da afetividade no processo de ensino-aprendizagem especialmente na etapa da Educação Infantil em que essa dimensão se faz extremamente presente. Apresentamos a relevância do tema para o contexto da Educação Infantil, seguida de análise da existência do mesmo no documento citado e posteriormente a forma como o referido assunto é abordado nesse documento. Para desenvolver e embasar a análise da temática proposta nesse trabalho utilizamos, sobretudo, a teoria psicogenética de Henri Wallon que considera o processo de desenvolvimento humano a partir de uma ótica integral, na qual a afetividade é um dos fatores determinantes nesse processo.
Keywords: Educação de crianças; Afetividade; Currículos; Education